Clown for Change - Cartoonist Marty Two Bulls as a Modern Heyoka - John, Sonja (Ethiopian Journal of Social Sciences, 2018)
Most Native American societies have trickster stories and roles which are used as an instrument for negotiating moral behavior. In Lakota country, the heyoka fulfills the clownish role to address taboos and sensitive issues. The late Severt Young Bear, Sr. noted that the heyoka no longer exists. Against this position, this article argues that the role and function of the traditional heyoka lives on in different art forms through highlighting the work of the renowned Oglala Lakota cartoonist Marty Two Bulls. By addressing sensitive issues like alcohol consumption in a humorous way, Two Bulls offers a space for new interpretations and renegotiation. In the past, due to the close link between representation and identity, Native cultural self-understanding has been adversely affected by stereotypes, most prominently the stereotype of the drunk Native. As a matter of cultural revitalization, Two Bulls uses this same interconnection as an opportunity for initiating change and encouraging Lakota to reclaim control over their lives. Through the lens of Native humor as a methodological tool to analyze cartoons, this article presents an example of how cultural productions can serve as an interpretive instrument and as a tool for tribal self-presentation.